A cognitive strategy scaffolding approach to facilitating reflection in engineering students. (2nd January 2016) - O'Shea, Peter; Kearney, Michael
Abstract: This paper provides an evidence-based methodology for fostering reflection during team projects in an engineering course. The approach is based on cognitive strategy scaffolding, a technique which has enjoyed much success in other contexts. The methodology has been implemented in a second-year mechatronics design unit, and the findings from a focus group and from independently conducted quantitative student evaluations show many (but not all) aspects of the method to be well received by both students and staff.